Training Complexity in Accordance with the Change in the Radius of the Jogging Curve in the Development of Some Physical Abilities and Mechanical Variables to Accomplish 200 Meter for Youth - Mazin Anhair Lami (Journal of Global Pharma Technology, 2016)
The objective of the research was to identify the effect of the special exercises to increase the training complexity according to the change in the radius of the jogging curve in the development of some physical abilities and biomechanical indicators and the achievement of running 200 m for youth. The sample of the research was short distance sprinters for the youth group within the clubs of Wasit province for the sports season 2017-2018. (12) Runner, the researcher used the experimental method of the two equal groups. And a set of standardized tests to measure physical capacity. The biomechanical variables were measured using cameras with a speed of 240 r / s and then analysis of the films by Kenova. The exercise was implemented by three training units per week with a total of (24) units, The tests were carried out by the pretest and post conditions and procedures and method of work, the researcher used the statistical bag (SPSS) to reach the test hypothesis of the search, a set of results to compare the experimental group and control were all significant results for the benefit of the experimental group in the brother except for the variable speed, the results were not significant.Keywords: Training complexity, Jogging curve physical abilities and mechanical variables.